Specific features of the parceling constructions in modern literary text (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is dedicated to the analysis of the structural and stylistic particularities of parceling constructions in modern literary text. The essence of the parceling phenomena as means of expressive syntax is specified, the basic types of parceling are determined and the principal stylistic functions of parceling are described.
Keywords: parceling; expressive syntax; principal and secondary parts of sentence; syntax construction